DESIGNING ENGLISH SPEAKING MATERIALS BY USING DIGITAL STORYTELLING PROJECT FOR THE ELEVENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL - Evrin Lorensya Br Sitepu; Indra Hartoyo; Rafika Dewi Nasution (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2024)
This study deals with the designing of English Speaking Materials By Using Digital Storytelling Project For The Eleventh Grade Students of Senior High School. The objectives of this study are: (1) to know the English speaking materials needed by grade eleventh students of senior high school, (2) to design appropriate English speaking materials by using digital storytelling project for the eleventh grade students of senior high school. This research was conducted at SMA Negeri 3 Medan. The research procedures of this study is Research and Development (R&D) through three phases : 1) evaluation and need analysis, 2) course design, and 3) materials validation. The instruments used were questionnaire, interview and documentation sheet. The data from evaluation and need analysis were analyzed by using descriptive technique and the data from expert judgement results were using quantitative data analysis. The result of this study is a course book of speaking materials by using digital storytelling project which consist of title, objective, introduction, observing, practices and reflection. The materials consist of three units, they are What Is Your Opinion, How May I Help You? and You Are Loved. Based on the experts‟ judgement result, the score was 3.97 which belongs to good category.